2008
DOI: 10.1016/j.humpath.2007.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic invasion revealed by multispectral imaging is common in primary melanomas and associates with prognosis

Abstract: Lymphatic invasion by tumor cells has been noted infrequently in primary melanomas. Our primary hypotheses were that using immunohistochemical markers of lymphatic vessels and of tumor cells would improve detection of lymphatic invasion and that lymphatic invasion would correlate with regional nodal metastatic disease. This study included 106 patients who were diagnosed between 1972 and 1991 and who had ≥ 10 years of follow up. We performed dual immunohistochemical stains for podoplanin (for lymphatic vessels)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 24 publications
6
64
0
Order By: Relevance
“…Co-expression of TP and CD68 was revealed by the Nuance System (Cambridge Research and Instrumentation Inc., Woburn, MA, USA) (32). Double-stained slides for TP and CD68 antibodies were imaged at x200 through a liquid crystal tunable filter.…”
Section: Determination Of Co-expression Of Tp and Cd68mentioning
confidence: 99%
“…Co-expression of TP and CD68 was revealed by the Nuance System (Cambridge Research and Instrumentation Inc., Woburn, MA, USA) (32). Double-stained slides for TP and CD68 antibodies were imaged at x200 through a liquid crystal tunable filter.…”
Section: Determination Of Co-expression Of Tp and Cd68mentioning
confidence: 99%
“…Furthermore, our results indicate that positive LYI status is related to poor outcome defined as shorter CSOS, DFS, as well as OS. Prognostic significance of LYI in the context of patient survival was demonstrated by several laboratories [3,6,28], while other groups did not confirm this observation [7,26,29].…”
Section: Discussionmentioning
confidence: 93%
“…1,11,17 Previously, we showed that OS and disease-specific survival durations were shorter for patients with LVI than for those without LVI, and that immunostaining-detected LVI and ulceration were associated significantly with OS. 9 Rose et al 11 found that immunostaining-detected LVI was a significant marker of both reduced DFS and OS.…”
Section: Survival Outcomesmentioning
confidence: 98%
“…Xu et al 17 showed that H&E alone detected LVI in 5 (5%) of 106 PCM, whereas dual immunostaining for podoplanin and S-100 and multispectral imaging analysis identified LVI in 35 patients (33%). Rose et al 11 assessed 246 primary melanomas for LVI using D2-40 immunostaining, CD34 immunostaining, and routine histology, and found that the use of endothelial markers increased the LVI detection rate (D2-40 and/or CD34, 18%, vs. routine histology, 3%).…”
Section: Detectionmentioning
confidence: 99%